Pengaruh Kualitas Produk, Brand Image Dan Personal Selling Terhadap Keputusan Pembelian Customer Di Gowwee Parfum Tunjungan Plaza Surabaya - Safina, Safina; Estik Hari Prastiwi (Cahaya Ilmu Bangsa, 2025)
The number of refill perfume businesses in Surabaya, makes customers make purchasing decisions, so many things need to be considered such as product quality, brand image, and personal selling. This study aims to prove and analyze the effect of product quality, brand image, and personal selling on purchasing decisions at Gowwee Parfum Tunjungan Plaza Surabaya. In this study using quantitative descriptive with primary data collection. The number of samples in this study was 80 respondents. Data processing using multiple linear regression with the SPSS v30 program. The results of the study showed that the t-test showed that the variables Product Quality, Brand Image, and Personal Selling partially had a significant effect on Purchasing Decisions. The Product Quality variable showed t-count <t table (-8.867 < 1.992) and a probability value of 0.001 < 0.05 so that it was negative and had a significant effect on Purchasing Decisions, this shows that product quality can improve consumer attitudes in purchasing decisions. In the Brand Image variable shows t-count> t-table (10.437 > 1.992) and a probability value of 0.001 <0.05 so that it has a positive value and has a significant effect on Purchasing Decisions, this shows a strong brand image in the minds of consumers provides loyal behavior, satisfaction, and commitment to the brand so that the better the brand image, the greater the purchasing decision. In the Personal Selling variable shows t-count > t-table (8.420 > 1.992) and a probability value of 0.001 < 0.05 so that it has a positive value and has a significant effect on Purchasing Decisions, this shows that consumers can easily reach the product, the transaction process is easier to do, so the better the personal sales, the greater the purchasing decision. Based on the F test shows F-count > F-table (66.125 > 2.49) and the probability value is 0.001 < 0.05 so that the variables of Product Quality, Brand Image, and Personal Selling simultaneously or together have a significant effect on the Purchasing Decision variable in the Gowwee Parfum Tunjungan Plaza Surabaya business. Based on the multiple linear regression analysis obtained the equation Y = 8.808 - 0.777 X1 + 1.295 X2 + 0.734 X3 + e, where the constant is 8.808, while the coefficient value of each variable against Y so that for X1 of -0.777 indicates the opposite direction, for X2 of 1.295 indicates the same direction, and for X3 of 0.734 indicates the same direction. Based on the determination coefficient test (R2) shows the p ercentage contribution of the influence of each variable X on the variable Y of 72.3%, while the remaining 27.7% is influenced by other variables. Keywords : Purchasing Decision, Product Quality, Brand Image, Personal Selling.